Prophet Muhammad and His Western Critics: A Critique of W. Montgomery Watt and Others by Zafar Ali Qureshi, Idara Ma'arif Islamic, Lahore, 1992, 2 Vols, p. 1103. (American Journal of Islam and Society, 2001)
This book by the Pakistani scholar Zafar Ali Qureshi is devoted to animportant aspect of the relationship between Islam and the West.The image of the Prophet Muhammad (pbu) produced by western scholarsof Islam has determined, in many ways, the parameters of the relationshipbetween the two religions and the respective civilizations to which theyhave given rise. The main argument of Qureshi's extremely well-researchedbook is that the western scholarship bred by the centuries-oldChristian prejudices against Islam has tried to undermine the religious andintellectual basis of Islam by undermining the central place and authority ofthe Prophet of Islam. This strategy was in no way accidental, because theChristian conception of religion takes as the basis of the Divine revelationnot the revealed book, i.e., the Qur'an or the Bible, but Jesus Christ. Seenthrough the eyes of Christology, Islam could not be anything other than'Muhammadanism', and any scholarly treatment of it was bound to bebased on the figure of the Prophet of Islam. It was within this frameworkthat a number of historicist and materialist accounts were given to provethat the Prophet Muhammad was not an authentic prophet and that hismotives were basically political, tribal or economic.The number of books produced in this line of spurious scholarship isimmense, and Qureshi has carried out an immense survey of westernliterature on the life and personality of the Prophet. Although the authorspans through hundreds of books produced in the West, he focuses on thework of Rev. Montgomery Watt, the celebrated western scholar of Islam.The reason for this concentration is that Watt's two-volume work on the ...